Multi-stable configurations for vibration-based energy harvester - Wileen Kristanto (2014)
The world waits for a better battery. The battle to build the ultimate battery is intensifying, as the world is faced with growing global demand for wireless gadget lifestyle. The constraint in the battery life poses a form of challenge in our lives. For this reason, thousands of dollars are being channelled into the research for methods to harvest energy from the environment. To date, one of the more promising advances is vibration energy harvesting. Vibration energy stands to be one of the most abundant, yet the possibly least tapped resource. This study of energy harvesting is to utilize the energy present in vibrations and convert it to a usable form using energy harvesters. Although this research has been around for the past few years, it has seen many drawbacks to the bandwidth of the operation for the energy harvester. Therefore, this study proposes to introduce multi-stable configurations with the use of magnets, to induce non-linearity. Non-linearity brings about more stable equilibrium states in the system, resulting in a broadened bandwidth of operation for the energy harvester. Also, this project also aims to study the optimization of non-linear configuration to further enhance the efficiency of the energy harvester with the use of single and dual magnets places at the ends of the cantilever. Researchers today are in the process of increasing the efficiency of piezoelectric harvesting. This report will illustrate and analyse the linear and non-linear experiment for the Bimorph, Fibreglass, and Aluminium cantilever beam, as well as discuss the future work of the research.